Screening and identification of serum biomarkers of osteoarticular tuberculosis based on mass spectrometry. Issue 7 (12th March 2020) - Chen, Ximeng; Jia, Xingwang; Lei, Hong; Wen, Xinyu; Hao, Yanfei; Ma, Yating; Ye, Jingyun; Wang, Chengbin; Gao, Jimin
Abstract: Background: In view of the current difficulty of clinically diagnosing osteoarticular tuberculosis, our aim was to use mass spectrometry to establish diagnostic models and to screen and identify serum proteins which could serve as potential diagnostic biomarkers for early detection of osteoarticular tuberculosis. Methods: Matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) was used to select an osteoarticular tuberculosis‐specific serum peptide profile and establish diagnostic models. Further, liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) was used to identify potential serum biomarkers that could be used for auxiliary diagnosis of osteoarticular tuberculosis, and then clinical serum samples were used to verify these biomarkers by enzyme‐linked immunosorbent assay (ELISA). Results: We established four diagnostic models that can distinguish osteoarticular tuberculosis from rheumatoid arthritis, ankylosing spondylitis, osteoarticular infections, and healthy adults. The models were osteoarticular tuberculosis‐rheumatoid arthritis, osteoarticular tuberculosis‐ankylosing spondylitis, osteoarticular tuberculosis‐osteoarticular infections, and osteoarticular tuberculosis‐healthy adult, and their accuracy was 76.78%, 79.02%, 83.77%, and 88.16%, respectively. Next, we selected and identified 18 proteins, including complement factor H‐related protein 1 (CFHR1) and complement factor H‐related protein 2 (CFHR2), which were upregulated in the tuberculosis group only. Conclusions: We successfully established four diagnostic models involving osteoarticular tuberculosis, rheumatoid arthritis, ankylosing spondylitis, osteoarticular infections, and healthy adults. Furthermore, we found that CFHR1 and CFHR2 may be two valuable auxiliary diagnostic indicators for osteoarticular tuberculosis. These results provide reference values for rapid and accurate diagnosis of osteoarticular tuberculosis.